Diagnostics Of Educational Achievements Is From Theme «HTML» (Journal of Information Technologies in Education (ITE), 2009)
Application of the automated current testing during teaching of informatics is examined from point of pedagogical diagnostics. Advantages of the automated testing and feature of test diagnostics of educational achievements are determined. A multiple test is offered for the current testing from theme «HTML», his structure is grounded.
Keywords: informatics; pedagogical diagnostics; test